2016
DOI: 10.1111/jzs.12159
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships inKerkiaand introgression betweenHauffeniaandKerkia(Caenogastropoda: Hydrobiidae)

Abstract: Freshwater truncatelloidean gastropods include numerous minute cryptic species, displaying simple morphologies, all of which hampers their taxonomic research based on morphology. Phylogenetic relationships among all but one extant species of the genus Kerkia from five localities in Croatia and one in Slovenia were therefore analysed based on one mitochondrial (cytochrome c oxidase subunit I) and three nuclear markers (18S, 28S and H3). Kerkia kusceri (Bole, ), K. jadertina Kuščer, 1933, K. j. sinjana (Kuščer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…They provided descriptions and illustrations of the shells, protoconchs, radulae, and soft part morphology and anatomy as well for all the three Croatian taxa. Rysiewska et al (2017) demonstrated molecular distinctness of those species of Kerkia.…”
Section: Introductionmentioning
confidence: 91%
“…They provided descriptions and illustrations of the shells, protoconchs, radulae, and soft part morphology and anatomy as well for all the three Croatian taxa. Rysiewska et al (2017) demonstrated molecular distinctness of those species of Kerkia.…”
Section: Introductionmentioning
confidence: 91%
“…For the Trebišnjica Basin and the northward areas, the following stygobiotic and crenobiotic genera are typical, viz. Mytilopsis Conrad, 1958;Travunijana Grego & Glöer, 2019;Emmericia Brusina, 1870;Belgrandia Bourguignat, 1869;Hadziella Kuščer, 1932;Kerkia Radoman, 1978;Narentiana Radoman, 1973;Belgrandiella A. J. Wagner, 1928;Dalmatinella Radoman, 1973;Sadleriana Clessin, 1890;Tanousia Servain, 1881 and an undescribed genus represented by "Pseudamnicola" troglobia Bole 1961 (Kuščer 1933, Schütt 2000Bilandžija et al 2013;Beran et al 2014Beran et al , 2016Rysiewska et al 2017;Hirschfelder 2018, Falniowski et al 2021. The above listed genera cannot be found in the Skadar Lake Basin (the Drin River system) and its associated Kotor Bay drainage basin, which have their typical freshwater malacofauna consisting of gastropod genera such as: Bracenica Radoman, 1973;Anagastina Radoman 1978;Stygobium Grego & Glöer, 2019;Karucia Glöer & Pešić, 2013;andZeteana Glöer &Pešić, 2014 (Reischütz andReischütz 2008;Glöer 2012, 2013a, b;Reischütz et al 2013Reischütz et al , 2014Reischütz et al , 2016Glöer and Pešić 2014a, b;Grego et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Chertoprud et al (2016) summarised the species detected during their research in the southeast Caucasus. Nevertheless, it was clear from the above works and from recent studies of the Balkan fauna (Szarowska 2006;Beran et al 2015Beran et al , 2016Rysiewska et al 2017;Grego et al 2018;Hofman et al 2018;Osikowski et al 2018;Grego et al 2019), that the Caucasian species were assigned to respective Balkan genera (Belgrandiella, Paladilhiopsis, Plagigeyeria) based only on the few morphological features of the shell, and it is not likely that they are closely related to the geographically distant morphotypes. Molecular investigations of genus Belgrandiella from Georgia (Grego et al 2017) revealed its close relationship to the genus Agrafia Szarowska & Falniowski, 2011 from Greece.…”
Section: Introductionmentioning
confidence: 99%